Clothianidin alters leukocyte profiles and elevates measures of oxidative stress in tadpoles of the amphibian, Rana pipiens. (1st September 2021) - Robinson, Stacey A.; Chlebak, Ryan J.; Young, Sarah D.; Dalton, Rebecca L.; Gavel, Melody J.; Prosser, Ryan S.; Bartlett, Adrienne J.; de Solla, Shane R.
Abstract: Neonicotinoid pesticide use is widespread and highly debated, as evidenced by recent attention received from the public, academics and pesticide regulatory agencies. However, relatively little is known about the physiological effects of neonicotinoid insecticides on aquatic vertebrates. Amphibians (larval stages in particular) are excellent vertebrate bioindicators in aquatic systems due to their risk of exposure and sensitivity to environmental stressors. Previous work with wood frog ( Rana sylvatica ) tadpoles exposed to formulated products containing thiamethoxam or clothianidin in outdoor mesocosms found significant shifts in leukocyte profiles, suggesting the tadpoles were physiologically stressed. The main objective of the present study was to characterize this stress response further using complementary measures of stress after exposure to clothianidin on northern leopard frogs ( Rana pipiens ) during their aquatic larval stages. Laboratory static-renewal exposures were conducted over eight weeks with the technical product clothianidin at 0, 0.23, 1, 10 and 100 μg/L, and diquat dibromide at 532 μg/L was used as a positive control. We assessed tadpole leukocyte profiles and measures of oxidative stress as these sub-lethal alterations could affect amphibian fitness. We found changes in several types of leukocytes at 1 and 10 μg/L, suggesting that these tadpoles exhibited signs of mild physiological stress. Clothianidin also induced an oxidative stress response at 0.23, 1 and 100 μg/L. However, we found no differences in survival, growth, development time or hepatosomatic index in frogs exposed to clothianidin. Our study indicates that tadpoles chronically exposed to clothianidin have increased stress responses, but in the absence of concentration-response relationships and effects on whole-organism endpoints, the implications on the overall health and fitness of these changes are unclear. Graphical abstract: Image 1 Highlights: We chronically exposed northern leopard frog tadpoles to clothianidin Exposure to clothianidin altered ratios of some leukocytes at 1 and 10 μg/L Clothianidin induced an oxidative stress response at 0.23, 1 and 100 μg/L Exposure to clothianidin did not affect growth, development or hepatosomatic index Exposure to clothianidin caused a mild stress response in northern leopard frogs Abstract : Clothianidin, a neonicotinoid, induces mild stress responses in tadpoles.